Linguistic differences between well‐established and predatory journals: a keyword analysis of two journals in political science. Issue 3 (3rd June 2019) - Soler, Josep; Wang, Ying
Abstract : Predatory publishing has become a much‐discussed and highly visible phenomenon over the past few years. One widespread, but hardly tested, assumption is the idea that articles published in predatory journals deviate substantially from those published in traditional journals. In this paper, we address this assumption by utilizing corpus linguistic tools. We compare the 'academic‐like' nature of articles from two different journals in political science, one top‐ranking and one alleged predatory. Our findings indicate that there is significant linguistic variation between the two corpora along the dimensions that we test. The articles display notable differences in the types and usage of keywords in the two journals. We conclude that articles published in so‐called predatory journals do not conform to linguistic norms used in higher‐quality journals. These findings may demonstrate a lack of quality control in predatory journals but may also indicate a lack of awareness and use of such linguistic norms by their authors. We also suggest that there is a need for the education of authors in science writing as this may enable them to publish in higher‐ranked and quality‐assured outlets.